Taking Nazi technology : Allied exploitation of German science after the Second World War - O'Reagan, Douglas (Baltimore: Johns Hopkins University Press, 2019)
This is a work of original research in the field of the history of science and technology. Following WWII, the Allies attempted the largest forced technology transfer in history by extracting intellectual reparations from occupied Germany. In nearly every field of science and technology, the Western allies--the US, UK, France, and USSR--assembled teams of experts who scoured defeated Germany seeking industrial secrets and those who could explain them. The book argues that these efforts changed international ideas of what it takes to transfer technology and were themselves shaped by how policy makers saw science fitting into society.--
Introduction -- American postwar scientific exploitation and the myth of German technological superiority -- British scientific exploitation and the allure of German know-how -- French planning for German science : student spies and exploitation in place -- Soviet reparations and the seizure of German science and technology -- Academic science and the reconstruction of Germany -- Documentation, microfilm, and information technology : the exploitation of German science and the information overload of the twentieth century -- Legacies of intellectual reparations programs : industrial know-how in the postwar world -- Conclusion.
Includes bibliographical references (pages [255]-272) and index.
Keywords: Technology transfer -- Germany -- History -- 20th century; World War, 1939-1945 -- Reparations; World War, 1939-1945 -- Science; Military research -- Germany -- History -- 20th century